Research on failure mechanism of final drive gears of a passenger car based on multi-condition varying-speed accelerated test - Haibo Yu; Hongyu Hu; Yuzhuo Men; Mingda Li; Bingkui Ji; Xueping Yao (Advances in Mechanical Engineering)
To standardize the reliability test evaluation schedule of passenger cars powertrain, a multi-condition varying-speed accelerated test criteria correlated with the statistical data of target vehicles is developed. With this test criteria, a real-vehicle test is conducted to evaluate a trial-manufacture car equipped with a newly developed transmission. Regarding the fracture failure of the driving and driven gears of the final drive, a heat treatment quality inspection is conducted on the fractured gears. From the meshing state of the gears, it is observed that machining precision errors caused an excessively large bearing clearance of the helical gear in the differential housing, with the meshing area of the driving gear tilting to one side and generating eccentric loads under uneven stress. The fatigue damage of the gears is calculated by the rainflow cycle matrix of the gears obtained with the rotating rainflow counting method. The calculation results show that largest loads transmitted by the final drive gears in varying-speed test condition 2, which was the main condition for fractures of the driven gear. Under this condition, the driving gear also produced bending fatigue failure due to the significant-amplitude cyclic loading caused by the eccentric loads.